An Analysis of Expenditure Pattern of Farm Families in Prayagraj District of Uttar Pradesh - Kumari, Pushpa; Dixit, Sunita (Journal of Extension Education, 2024)
The study was conducted in the Chaka and Kundhiyama blocks situated in Prayagraj district of Uttar Pradesh, India. Altogether, 200 farmers were randomly selected from four villages of the selected blocks. The results of the study revealed that the average monthly family expenditure increased as the land size increased, except in the case of medium-sized farm-holders, as the average family size was larger than that of small-sized farm holders. The percentage of expenditure was found to be more on food; it was found that the percentage of the amount spent on food decreased as the income increased. The percentage of expenditure on food items decreased with the increase in holding size.